Avaliação in vitro do potencial anticárie de selantes resinosos e ionoméricos contendo digluconato de clorexidina - Vieira, Pedro Henrique Acioly Guedes Peixoto (2016)
Sealants are materials applied to scars and fissures to prevent onset the onset of the caries process or interrupt its progression. Chlorhexidine (CLX) is a broad spectrum antimicrobial agent whose incorporation has been tested in various dental materials. The objective of this study was to evaluate the in vitro effect of the incorporation of chlorhexidine digluconate (DC) at 0.5% on the properties of a resinous sealant (SR) and a chemically activated ionomeric sealant (SI). The effect of the incorporation of CLX on the roughness of the materials was also evaluated. (Bioseal®-control group), SRDC (Bioseal® + 0.5% DC), SI (Riva Protect®) and SIDC (Riva Protect®) + 0.5% of DC). For an enamel caries induction, a microbiological model of S. mutans biofilm formation was used for five days, three blocks of each group for each experimental triplicate. The antimicrobial effect was evaluated by counting UFCs (colony forming units), dry weight analysis and confocal microscopy.To evaluate the demineralization, the blocks were analyzed by longitudinal microhardness of the enamel at 50 μm and 100 μm of the restoration margin. In addition, for each experimental group, test specimens from all groups were analyzed for their surface roughness pattern. Data were analyzed using ANOVA (two factors), with significance level of 5%. SR presented fewer CFUs when compared to SI (p = 0.004). Regarding dry weight, SR was lower than SI (p = 0.006). In the analysis of hardness at 50 μm, lower demineralization was observed for groups with ionomer when compared to those with resin (p <0.001), as well as between groups with CLX when compared to groups without CLX (p = 0.026). In the distance of 100 μm, the groups with ionomer showed a lower demineralization when compared to those with resin (p <0.001). The roughness in SI was superior to SR, both before (p = 0.032) and after exposure to cariogenic biofilm (p <0.001). In general, confocal laser microscopy (MCLS) data provided information consistent with the efficiency of CLX incorporation favoring the antimicrobial activity of resinous sealants when compared to ionomeric sealants. The ionomeric materials have a higher anticaryeffect, however the incorporation of DC seems to be more effective and necessary when using resinous sealants.